Business Strategy Analysis in Increasing Sales of Dates in Bandar Lampung - Hafidz A., Umar; Rusdi, Zainnur M. (Basecamp Economics PubMed, 2024)
This research aims to analyze the impact of business strategies on increasing date sales in the city of Bandar Lampung. The study uses a quantitative method with a descriptive approach to identify the strategies implemented by date sellers and their influence on consumer purchasing decisions. Data was collected through direct observation, interviews with date shop owners, and sales data from date shops in Bandar Lampung over a specific period. The results show that date sales significantly increased during the month of Ramadan compared to other months. However, other factors such as pricing, promotions, and marketing strategies also play a crucial role in influencing consumer purchasing decisions. This research provides recommendations for business owners to focus more on product diversification and marketing innovations to boost sales throughout the year, not just during Ramadan.